Réponses

2013-10-25T12:59:43+02:00
A = 3 ( x - 10 ) ( x + 10 ) + ( 2x + 5 ) ( x + 10 )
= 3 * x + 3 * (-10) + 3 * x + 3 * 10 + 2x * x + 2x * 10 + 5 * x + 5 * 10
= 3x - 10 + 3x + 30 + 2x^2 + 20x + 5x + 50
= 31x + 70 + 2x^2 

B = 4 ( 3x + 6 ) ( 5x + 1 ) - 2 ( 3x - 6)²
= 4 * 3x + 4 * 6 + 4 * 5x + 4 * 1 - 2 * 3x^2 - 2 * (-36)
= 12x + 24 + 20x + 4 - 6x^2 + 72
= 32x + 100 - 6x^2

C = 4 ( 7x + 5 )² + 4 ( 2x - 1 ) ( 7x + 5 )
= 4 * 7x^2 + 4 * 25 + 4 * 2x + 4 * (-1) + 4 * 7x + 4 * 5
= 26x^2 + 100 + 8x - 4 + 28x + 20
= 26x^2 + 116 + 36